590 The influence of physiological parameters on game efficiency in team handball (Balneo and PRM Research Journal, 2024)
In addition to the technical and tactical aspects, the influence of physiological parameters is an important aspect for the performance of handball players. In this paper, the authors aim to highlight and analyze the influence of specific indices on efficiency in the game. For this purpose, a methodology based on experimental physiological measurements and modeling with artificial neural networks (ANN) was used. The obtained results allow to conclude that the total efficiency coefficient in the game (CECG) is influenced by the measured values of the specific physiological indices. In addition, the use of the ANN can identify opportunities to improve CECG by changing these indices and, in this case, replacing pre-game inactivity (PB) with a program (AB) to maintain physiological parameters at optimal levels.